MINAT BELAJAR DI MASA PANDEMI COVID – 19 DALAM HUBUNGANNYA DENGAN HASIL BELAJAR KELAS IV - Desi Meliana; Budiman Tampubolon; Hery Kresnadi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2022)
AbstrakThis study aims to describe Students' Interest in Learning During the Covid-19 Pandemic in Relation to Learning Outcomes in Class IV Thematic Learning at Kartika XVII-1 Elementary School Pontianak. The method used is a descriptive method in the form of relationship studies (interrelationship studies) using a correlation study research method (correlation studies). This research is a population study with a total of 25 students. Data collection techniques in this study are interview techniques, questionnaires (questionnaire) and document collection. The data collection tools used are questionnaires and documents on the average value of students' daily tests. The results showed that 83.20% of students' interest in thematic learning during the Covid-19 pandemic at Kartika XVII-1 Pontianak Elementary School was 83.20% in the "Good" category, while the learning outcomes of fourth graders at Kartika XVII-1 Pontianak Elementary School had an average score of - The overall daily test average is 55.50. Results Based on calculations using the product moment correlation formula for the calculation of students' thematic learning interest with learning outcomes obtained rcount of 0.014, while rtable of 0.413 means rcount < rtable or (0.014 < 0.431). Results Based on the research, the students' thematic learning interest during the Covid19 pandemic with the learning outcomes of fourth graders at Kartika XVII-1 Pontianak Elementary School did not have a positive relationship and the correlation level was included in the very low category.Keywords: Learning Interests, Learning Outcomes, Relationships, Thematic Learning